Environmental Accounting and Reporting of Agricultural Enterprises - A. V. Chepulyanis; R. R. Sadykov (Учёт. Анализ. Аудит)
The paper describes the problems of increasing the openness of information about environmental protection activities and meeting the requirements of environmental and industrial safety by domestic enterprises within the framework of their economic activities. The authors consider theoretical and methodological aspects of the organization of ecological accounting and the formation of environmental reporting. This is an effective tool for assessing the results achieved by using nature and environmental activities of the organization. Also, it improves the level of industrial safety and environmental culture at the enterprise, using disclosure and analysis of environmental factors of sustainable development of an economic entity. The research reveals the economic essence and gives the author’s interpretation of the definitions “environmental accounting”, “environmental reporting”, “natural capital”, “environmental obligation”. The authors tried to systematize the regulatory framework for the formation of environmental reporting from the perspective of stakeholders, as well as present the classification and systematization of environmental indicators of sustainable development of the organization included in integrated reporting. The study revealed the structure of the subsystem of environmental accounting and its place in the system of accounting and analytical support of an economic entity is determined. The authors proposed mechanisms for improving the accounting of environmental obligations, real and conditional costs for nature management and ecology. The methodological basis of the study comprised systematic and dialectical approaches, as well as a set of general scientific and special methods of cognition: observation, systematization and generalization, methods of classification and grouping. The object of the study was the reporting of the largest Russian enterprises of various industries.